The role of SDF-1/CXCR4 in the vasculogenesis and remodeling of cerebral arteriovenous malformation - Wang L; Guo S; Zhang N; Tao Y; Zhang H; Qi T; Liang F; Huang Z (Dove Medical Press, 2015)
Lingyan Wang,1 Shaolei Guo,2 Nu Zhang,2 Yuqian Tao,3 Heng Zhang,1 Tiewei Qi,2 Feng Liang,2 Zhengsong Huang2 1Department of Neurosurgery ICU, 2Department of Neurosurgery, 3Department of Neurology, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People’s Republic of China Background: Cerebral arteriovenous malformation (AVM) involves the vasculogenesis of cerebral blood vessels and can cause severe intracranial hemorrhage. Stromal cell-derived factor-1 (SDF-1) and its receptor, CXCR4, are believed to exert multiple physiological functions including angiogenesis. Thus, we investigated the role of SDF-1/CXCR4 in the vasculogenesis of cerebral AVM.Methods: Brain AVM lesions from surgical resections were analyzed for the expression of SDF-1, CXCR4, VEGF-A, and HIF-1 by using immunohistochemical staining. Flow cytometry was used to quantify the level of circulating endothelial progenitor cells (EPCs). Further, in an animal study, chronic cerebral hypoperfusion model rats were analyzed for the expression of SDF-1 and HIF-1. CXCR4 antagonist, AMD3100, was also used to detect its effects on cerebral vasculogenesis and SDF-1 expression.Results: Large amounts of CXCR4-positive CD45+ cells were found in brain AVM lesion blood vessel walls, which also have higher SDF-1 expression. Cerebral AVM patients also had higher level of EPCs and SDF-1. In chronic cerebral hypoperfusion rats, SDF-1, HIF-1, and CD45 expressions were elevated. The application of AMD3100 effectively suppressed angiogenesis and infiltration of CXCR4-positive CD45+ cells in hypoperfusion rats compared to controls.Conclusion: The SDF-1/CXCR4 axis plays an important role in the vasculogenesis and migration of inflammatory cells in cerebral AVM lesions, possibly via the recruitment of bone marrow EPCs. Keywords: cerebral arteriovenous malformation, SDF-1/CXCR4, chronic cerebral hypoperfusion, endothelial progenitor cells